First observations of attempted nudibranch predation by sea anemones - van der Meij, S; Reijnen, B (Springer-Verlag, 2011)
On two separate occasions during fieldwork in Semporna (eastern Sabah, Malaysia), sea anemones of the family Edwardsiidae were observed attempting to feed on the nudibranch species Nembrotha lineolata and Phyllidia ocellata. These are the first in situ observations of nudibranch predation by sea anemones. This new record is compared with known information on sea slug predators.